Interactive effects of acolour wheel motion game on pupils’ cognitive development in graphic arts - Olubunmi Odewumi, Micheal; Olusola Otunla, Adekunle; Abass Bada, Tayo (Revija za elementarno izobraževanje, 2020)
Games can be instruments for fun and competition globally. However, despite their relevance for instruction, the awareness of key games and their use have not been significantly established. Therefore, the study investigates the interactive effects of colour wheel motion games on pupils' cognitive development in the field of graphic arts. The study included a pre-test and a post-test. The sample comprised 50 pupils: 25 boys and 25 girls. Two research hypotheses were tested. Findings revealed a significant difference between groups (experimental and control) and gender (boys and girls). Nevertheless, the use of the Colour Wheel Motion Game for learning was recommended for all pupils in secondary schools in Nigeria.
Keywords: Colour; Creative Arts; Game; Gender; Graphic arts